Synthesis Oxalic Acid from Durian skin (Durio Zibethinus) with Alkali Smelting Method - Hutagalung, Johannes Martua (Universitas Insan Cendekia Mandiri, 2024)
Durian (Durio zibethinus) , nicknamed The King of Fruit, is a fruit that is quite popular in Indonesia. This prickly fruit which has a pungent aroma and distinctive taste is very popular with many people. The edible part of the fruit (percentage of fruit flesh weight) is low, which is only around 20.52%, this means that there are around 79.48% which is the part that is not utilized for consumption such as the skin and seeds of the durian fruit. So, there is a lot of durian skin waste that will be produced. Durian fruit skin contains lignocellulosic materials, namely cellulose, hemicellulose, and lignin. Based on the data above, we want to utilize durian skin waste in research on the manufacture of oxalic acid. To make oxalic acid from durian fruit peel waste, we use the alkaline smelting method with several stages, namely: precipitation with CaCl2, acidification with H2SO4 and crystallization. The alkali used was NaOH with various concentrations of 3N, 4N, and 5N with cooking times of 30, 40, and 60 minutes at a temperature of 95oC. The optimum concentration of NaOH and optimum melting time to make oxalic acid from durian fruit peel waste was at the solution concentration. NaOH 4N and a time of 60 minutes with a weight % Yield of 6,95%.